2021
DOI: 10.3390/cells10010189
|View full text |Cite
|
Sign up to set email alerts
|

P2X7 Variants in Oncogenesis

Abstract: The P2X7 receptor for extracellular ATP is a well-established mediator of tumoral development and progression both in solid cancers and hematological malignancies. The human P2X7 gene is highly polymorphic, and several splice variants of the receptor have been identified in time. P2X7 single-nucleotide polymorphisms (SNPs) have been broadly analyzed by studies relating them to pathologies as different as infectious, inflammatory, nervous, and bone diseases, among which cancer is included. Moreover, in the last… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
43
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(44 citation statements)
references
References 105 publications
1
43
0
Order By: Relevance
“…One of the relevant purinergic receptors is the P2X7 receptor (P2X7R), as it is involved in several patho-/physiological processes, such as pancreatic cancer [22,23], inflammation [24] and pain [25]. The P2X7R belongs to the P2X ion channel/receptor family and is encoded by a highly polymorphic gene [26][27][28][29] with some single nucleotide polymorphisms correlating with human diseases (chronic lymphocytic leukemia, osteoporosis and pain) [27,30,31]. Moreover, there are also different splice isoforms of the P2X7R, A-J in humans and A and K in rodents, where A are regarded as the common full-length variants [26,32].…”
Section: Introductionmentioning
confidence: 99%
“…One of the relevant purinergic receptors is the P2X7 receptor (P2X7R), as it is involved in several patho-/physiological processes, such as pancreatic cancer [22,23], inflammation [24] and pain [25]. The P2X7R belongs to the P2X ion channel/receptor family and is encoded by a highly polymorphic gene [26][27][28][29] with some single nucleotide polymorphisms correlating with human diseases (chronic lymphocytic leukemia, osteoporosis and pain) [27,30,31]. Moreover, there are also different splice isoforms of the P2X7R, A-J in humans and A and K in rodents, where A are regarded as the common full-length variants [26,32].…”
Section: Introductionmentioning
confidence: 99%
“…Whilst P2X7R functionality is not fully assessed in every cancer type, some cancers studies have demonstrated that the receptor retains its functionality and is able to drive processes such as increased tumour cell survival via several different mechanisms [14,16,18,40]. Several other splice variants of P2X7R have also been identified in recent years, such as P2X7 isoform B and nfP2X7 with studies increasingly indicating them as potential biomarkers and therapeutic targets [41].…”
Section: P2x7r In Cancermentioning
confidence: 99%
“…The P2X7 receptor can be assembled by just one of them or by a composition of two or three different isoforms [ 42 ]. P2X7 receptor-related functions in physiological or oncological processes are associated with the expression levels of its genetic variants [ 43 , 44 ]. Among them, P2X7A and B isoforms are the most studied in humans.…”
Section: The Purinergic Signaling System—structural Insights Focusing On the P2x7 Receptormentioning
confidence: 99%
“…Among them, P2X7A and B isoforms are the most studied in humans. P2X7A has a C-terminal crucial for opening membrane large pores causing apoptosis, while P2X7B has a reduced C-terminal, being incapable of inducing cell death [ 11 ], while it is able to promote proliferation of stem and tumor cells [ 43 , 44 ] and participates in the cell differentiation process [ 44 ]. Although the role of isoforms for cancer metabolism reprogramming and metabostemness has been clarified yet, we hypothesize that a differential contribution of these isoforms account for cancer cell survival and self-renewal, metastasis and chemoresistance.…”
Section: The Purinergic Signaling System—structural Insights Focusing On the P2x7 Receptormentioning
confidence: 99%